تسريد المحلي ونسق الإغتراب في رواية الكناس سليم عبادو - منيرة , بدة زكري; الساكر, صبرينة (University of Eloued جامعة الوادي, 2024)
تهدف الدراسة إلى التعرف على التسريد المحلي ونسق الإتراب في رواية الكناس لسليم عبادو، حيث تمكن أهمية هذا البحث في الكشف عن أنساق الإغتراب الظاهرة منها والمضمرة و سردنة المحلي التي وظفها الكاتب "سليم عبادو"، وقد تم الاعتماد على منهج النقد الثقافي بالإستعانة بأدوات النقد السميائي، و قد إستعنا في دراستنا هذه بمجموعة من المصادر والمراجع نذكر على رأسها المصدر الأول لهذه الدراسة والمتمثل في رواية الكناس "لسليم عبادو". وتوصلت من الدراسة إلى النتائج الآتية: - أن الرواية تتناول تاريخ وادي سوف و كيف كافح سكان أهل سوف للعيش في منطقة حارة جدا تفتقر إلى الماء، لكن بفضل جهودهم و ذكائهم حولوا هاته المنطقة من أرض قفار إلى جنات خضراء من النخيل. - أن سوق الوادي يعد ظاهرة سوفية بحتة، لا يجمع السلع والبضائع فحسب، بل فيه تراث السوافة وعاداتهم وتقاليدهم، كما تتمثل فيه الشخصية الوفية المليئة بالحيوية والذكاء والنشاط بكل مقوماتها وأبعادها النفسية والاجتماعية و الاقتصادية. - أن سكان الوادي تمسكوا بهاته الربوع الحارة وتأقلموا معها وتحدوا قساوة الصحراء بحكم ماضيهم البدوي الذي فرض عليهم المغامرة والتحدي لهاته الصعاب. - أن الإغتراب حالة يعانيها الفرد نتيجة لعوامل مؤثرة فيه سواءا كان هذا الإغتراب نفسي أو إجتماعي، أو مكاني أو لظروف محيطة به. The study aims to identify the local narration and the system of alienation in the novel "The Sweeper" by Salim Abbadou, as the importance of this research lies in revealing the systems of alienation, both apparent and implicit, and the local narration employed by the writer "Salim Abbadou". The cultural criticism method was relied upon with the help of semiotic criticism tools. In this study, we used a group of sources and references, most notably the first source of this study, represented by the novel "The Sweeper" by Salim Abbadou. The study reached the following results: - The novel deals with the history of Wadi Souf and how the people of Ahl Souf struggled to live in a very hot area that lacked water, but thanks to their efforts and intelligence, they transformed this area from a wasteland into green paradises of palm trees. - The valley market is a purely Sufi phenomenon, which not only brings together goods and merchandise, but also the heritage of the Suwaf, their customs and traditions, and it represents the loyal character full of vitality, intelligence and activity with all its psychological, social and economic components and dimensions. - The inhabitants of the valley held on to these hot regions and adapted to them and challenged the harshness of the desert due to their Bedouin past that imposed on them adventure and challenge to these difficulties. - Alienation is a state that the individual suffers as a result of factors affecting him, whether this alienation is psychological or social, or spatial or due to the surrounding circumstances.
أدب حديث ومعاصر
Keywords: تسريد المحلي، نسق الإغتراب، رواية الكناس، سليم عبادو; Narration of the local; the system of alienation; the novel of the sweeper; Salim Abbadou.